2004
DOI: 10.21273/jashs.129.1.0013
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Degradation in Detached Pome Fruit with Reference to Preharvest Red Color Loss and Pigmentation Patterns of Blushed and Fully Red Pears

Abstract: Exposed fruit of `Rosemarie' blushed pear (Pyrus communis L.) displayed daily fluctuations in color in response to temperature while color was more stable in other blushed and fully red cultivars. `Rosemarie' pears increased in redness with the passing of cold fronts, but rapidly lost red color during intermittent warmer periods. Studies on anthocyanin degradation in detached apples and pears indicated that preharvest red color loss was due to net anthocyanin degradation at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…In pear skin, red color fades toward harvest (Steyn et al 2004b), which is not common in other fruits such as apple (with higher anthocyanin content toward harvest), suggesting that anthocyanin synthesis in pear has unique features. In this study, the transcription of PyMYB10 and anthocyanin biosynthetic genes declined during late stages of fruit development, in agreement with the lower eYciency of anthocyanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pear skin, red color fades toward harvest (Steyn et al 2004b), which is not common in other fruits such as apple (with higher anthocyanin content toward harvest), suggesting that anthocyanin synthesis in pear has unique features. In this study, the transcription of PyMYB10 and anthocyanin biosynthetic genes declined during late stages of fruit development, in agreement with the lower eYciency of anthocyanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, anthocyanin biosynthesis and accumulation in pears appears to be more complicated. For example, the red skin apparently fades toward harvest (Steyn et al 2004b), and anthocyanin content decreases under strong light (Steyn et al 2004b). Evidence of the involvement of MYB, bHLH or other TFs in anthocyanin biosynthesis is largely lacking in pears, and whether these genes are induced by sunlight remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pulse-chase experiments with softened Cabernet Sauvignon berries demonstrated increased anthocyanin catabolism in parallel to decreased synthesis when growth temperatures were elevated, suggesting that both processes determine the final color of the grapes (Mori et al 2007). Similarly, loss of red pigmentation in pears and apples at elevated temperatures or decreased light intensities is a combination of less synthesis and increased catabolism (Huysamer 1998;Steyn et al 2004). Similar to observations in detached Cabernet Sauvignon grapes (Mori et al 2007), anthocyanin turnover was found in the cell suspension of V. vinifera cv.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding anthocyanin catabolism in fruit might enable its inhibition, leading to a significant increase in pigment accumulation in the plant tissues. Inhibition of anthocyanin degradation in fruit could be most valuable at elevated temperatures, during which there is an increase in the rate of pigment degradation (Huysamer 1998;Mori et al 2007;Steyn et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the puree used for the coatings exhibited a bright red color, acerola purees (and consequently the puree-based coatings) are highly susceptible to color fading, because of anthocyanin degradation during processing and storage (Bakowska et al, 2003), which results in color changes (Steyn et al, 2004). Indeed, the brownish pale-red color of AA-and CWAA-coated acerolas indicates loss of saturation and partial conversion of flavylium cation of the anthocyanins into colorless forms (De Rosso and Mercadante, 2007;Rodr铆guez-Saona et al, 1999), which explains why they were less accepted.…”
Section: Visual Acceptance and Colormentioning
confidence: 99%